Competing or non-competing the overlapping jurisdiction of the Philippine Competition Commission anode Philippine Transportation Agencies over sector-specific regulatory matters and competition issues (Philippine Law Journal, 2021)
Philippine transportation agencies, as sector regulators, and the Philippine Competition Commission (PCC), as the primary antitrust regulatory body of the Philippines, have overlapping jurisdiction over sector-specific matters and competition issues in the transportation industry. This jurisdictional dilemma is even reinforced by the vague wording of Section 32 of the Philippine Competition Act ("PCA"). The overlap became apparent when the Land Transportation Franchising and Regulatory Board (LTFRB) halted Uber's operations despite the order of the PCC to continue pending its merger review; it was also evident when the LTFRB imposed a biker cap on Angkas to preclude monopolistic behavior. To properly delineate, Philippine transportation agencies should exercise jurisdiction over sector-specific matters involving the transportation industry, since jurisdiction over the same was explicitly vested, domain expertise is exclusive to them, and the PCC is unable to overturn the decisions of sector regulators. At the same time, the PCC should take cognizance of competition issues in the transportation industry, considering that the PCA has expressly granted it jurisdiction over competition issues and the PCC is the agency mandated to enforce national competition policy. This Note then presents recommendations consistent with the United Nations Conference on Trade and Development to prevent jurisdictional conflict between these agencies.